The sauropodomorph dinosaurs from the Late Triassic (Norian) of Jameson Land, East Greenland - Campo, Victor Beccari Dieguez (2021)
The Late Triassic (Norian) outcrops of Malmros Klint Formation, Jameson Land, central East Greenland, are home to non-sauropod sauropodomorphs that are yet to be thoroughly described. The material recovered to this locality comprises of almost complete and sometimes articulated specimens, preserving both cranial and postcranial elements, and tracks. These fossils were briefly reported in the literature and were assigned to the taxon Plateosaurus trossingensis. However, with new findings for the clade of early non-sauropod sauropodomorphs around the globe, the material should be revised. The goal of the present thesis is to fully describe the specimens housed in Lourinhã Museum (ML), Lourinhã, Portugal, using μCT-Scan and Photogrammetry, when available, to understand the taxonomy, systematics and palaeobiogeography of these animals. The specimens in this study consist in two almost complete and articulated skulls. The Greenland sauropodomorph skulls were compared with other plateosaurid sauropodomorphs and closely related taxa for a full anatomical description. The specimens represent a single taxon of different ontogenetic stages, an early-stage juvenile (NHMD 164758) and a late-stage juvenile (NHMD 164741). This taxon differs from all other sauropodomorphs by a set of unique traits (1) the presence of a small foramen at the medial surface of the premaxilla at the base of the lateral process of the premaxilla; 2) an anteroposteriorly elongated dorsoposterior process of the squamosal; 3) a quadrate relatively tall in comparison to the rostrum height; 4) a well-developed, square-shaped in lateral view posterodorsal process of the articular) that are not explained by taphonomy, ontogeny and intraspecific variation. The Greenland sauropodomorph was recovered in the most recent phylogenetic analysis as the first non-Plateosaurus plateosaurid of Laurasia.